A Single Night of Partial Sleep Deprivation Induces Insulin Resistance in Multiple Metabolic Pathways in Healthy Subjects - Donga, Esther; van Dijk, Marieke; van Dijk, J. Gert; Biermasz, Nienke R.; Lammers, Gert-Jan; van Kralingen, Klaas W.; Corssmit, Eleonara P. M.; Romijn, Johannes A. (The journal of clinical endocrinology and metabolism, 2010)
Background: Subsequent nights with partial sleep restriction result in impaired glucose tolerance, but the effects on insulin sensitivity have not been characterized. Objective: The aim of this study was to evaluate the effect of a single night of partial sleep restriction on parameters of insulin sensitivity. Research Design and Methods: Nine healthy subjects (five men, four women) were studied once after a night of normal sleep duration (sleep allowed from 2300 to 0730 h), and once after a night of 4 h of sleep (sleep allowed from 0100 to 0500 h). Sleep characteristics were assessed by polysomnography. Insulin sensitivity was measured by hyperinsulinemic euglycemic clamp studies (from 1130 to 1430 h) with infusion of [6,6-2H2]glucose. Results: Sleep duration was shorter in the night with sleep restriction than in the unrestricted night (226 ± 11 vs. 454 ± 9 min; P< 0.0001). Sleep restriction did not affect basal levels of glucose, nonesterified fatty acids, insulin, or endogenous glucose production. Sleep restriction resulted in increased endogenous glucose production during the hyperinsulinemic clamp study compared to the unrestricted night (4.4 ± 0.3 vs. 3.6 ± 0.2 μmol×kg lean body mass−1 · min−1; P = 0.017), indicating hepatic insulin resistance. In addition, sleep restriction decreased the glucose disposal rate during the clamp (32.5 ± 3.6 vs. 40.7 ± 5.1 μmol · kg lean body mass−1 · min−1; P = 0009), reflecting decreased peripheral insulin sensitivity. Accordingly, sleep restriction decreased the rate of glucose infusion by approximately 25% (P = 0.001). Sleep restriction increased plasma nonesterified fatty acid levels during the clamp study (68 ± 5 vs. 57 ± 4 μmol/liter; P = 0.005). Conclusions: Partial sleep deprivation during only a single night induces insulin resistance in multiple metabolic pathways in healthy subjects. This physiological observation may be of relevance for variations in glucoregulation in patients with type 1 and type 2 diabetes.Partial sleep restriction during only a single night reduces insulin sensitivity of hepatic and peripheral glucose metabolism, as well as of peripheral lipolysis by 19–25%.